2021
DOI: 10.3892/ol.2021.12859
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of cytokinesis regulators PRC1, KIF14 and CIT has no prognostic role in colorectal and pancreatic cancer

Abstract: Colorectal cancer is one of the most common cancers and pancreatic cancer is among the most fatal and difficult to treat. New prognostic biomarkers are urgently needed to improve the treatment of colorectal and pancreatic cancer. Protein regulating cytokinesis 1 ( PRC1 ), kinesin family member 14 ( KIF14 ) and citron Rho-interacting serine/threonine kinase ( CIT ) serve important roles in cytokinesis, are strongly associated with cancer progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
3
1
Order By: Relevance
“…In the multivariate Cox model, accounting for additional covariates, the strength of the association increased and was statistically significant. Thus, the present investigation identified KIF14 expression as an independent favorable prognostic factor, although it was not reflected in the other report demonstrating that KIF14 gene expression did not affect the survival of CRC patients [42]. Contrary to the TCGA cohort used in the present study, the cited research was carried out on a relatively small cohort group of patients with little ethnic diversity, and cut-off values for high and low gene expression were established using different methods, which may explain the divergent results.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In the multivariate Cox model, accounting for additional covariates, the strength of the association increased and was statistically significant. Thus, the present investigation identified KIF14 expression as an independent favorable prognostic factor, although it was not reflected in the other report demonstrating that KIF14 gene expression did not affect the survival of CRC patients [42]. Contrary to the TCGA cohort used in the present study, the cited research was carried out on a relatively small cohort group of patients with little ethnic diversity, and cut-off values for high and low gene expression were established using different methods, which may explain the divergent results.…”
Section: Discussioncontrasting
confidence: 98%
“…According to our results, and unlike the data published for other examined cancers, KIF14 protein expression was downregulated in CRC tissues compared to the adjacent noncancerous tissues. In turn, KIF14 mRNA expression was upregulated in tumors compared to normal tissues, which is in line with the previous reports on various cancers, including colorectal cancer [ 37 , 38 , 39 , 40 , 41 , 42 ]. A mismatch between mRNA and protein levels has been frequently observed and extensively debated in the literature [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…CIT (Citron Rho-Interacting Serine/Threonine Kinase) is a gene encoding a serine/threonine-protein kinase that functions in cell division. Several recent studies have reported the potential role of CIT gene in the initiation and progression of some tumors [ 55 57 ]. The upregulation of CIT could promote the growth of cancer cells [ 56 , 57 ], and was associated with a poor outcome in some cancers such as bladder cancer and pancreatic ductal adenocarcinomas [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…CIT (Citron Rho-Interacting Serine/Threonine Kinase) is a gene encoding a serine/threonine-protein kinase that functions in cell division. Several recent studies have reported the potential role of CIT gene in the initiation and progression of some tumors [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Although this ratio was lower than that in Western European and American countries, the total number of colorectal cancer cases is still considerable due to the large population base in China [ 10 12 ]. In recent years, the incidence rate of colorectal cancer has shown a gradual increasing trend with the improvement of the living standard [ 13 ]. Surgery is the cornerstone of various treatments for colorectal cancer, but the surgical trauma is large, and patients suffer great physical and mental pain during perioperative period [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%